Ground‐based infrared thermometry reveals seasonal evapotranspiration patterns in semiarid rangelands. Issue 3 (2nd March 2023) - Hwang, Kyotaek; Chandler, David G.; Flerchinger, Gerald N.
Abstract: Detailed assessment of small‐scale heterogeneity in local surface water balance is essential to accurate estimation of evapotranspiration in semiarid climates. However, meteorological approaches are often impractical to implement in sites with sparse and diverse vegetation composition, especially with seasonally variable leaf canopy features. Ground‐based infrared thermometry (TIR) provides spatially and temporally continuous resolution of surface skin temperature that can be directly related to the land surface energy balance. We made repeated measurements with a portable TIR camera to capture seasonal replicates for patch scale heat images for four sagebrush communities. The heat images near peak foliage and near the end of the growing season were compared by computation of surface energy fluxes from TIR sensing to surface energy balance (SEB) and Bowen ratio (BR). Estimates of sensible ( H ) and latent heat flux ( LE ) were evaluated with eddy covariance measurements to disaggregate the expression of seasonal phenology of sagebrush species across wetness and elevation. Estimations showed reasonable agreement with ground‐based LE observations for most cases ( r 2  = 0.59–0.76 for SEB and 0.22–0.72 for BR; root mean squared error = 73.4–106.4 W m −2 for SEB and 109.9–204.0 W m −2 for BR). Predictability declined as the fraction of senescent foliage increased in dry conditions. The field trials suggest the methods have the potential for monitoring land surface energy fluxes and plant health at a very fine spatial scale. The ability to partition heat fluxes from various plant communities over a range of moisture availability will provide valuable information associated with the consumptive water use and phenological processes in the semiarid West. Abstract : Ground‐based thermal infrared (TIR) temperature can predict spatio‐temporally continuous land surface energy balance. Proposed TIR methods showed good agreement with ground‐based eddy covariance observations in turbulent heat fluxes for most cases. Predictability declined substantially as the fraction of senescent foliage increased in dry conditions.